Analisis Muatan Kurikulum Pendidikan Agama Islam Aspek Akhlak di SMP Negeri 2 Padangsidimpuan - Melva Zunaida; Magdalena Magdalena (Studi Multidisipliner: Jurnal Kajian Keislaman, 2021)
The purpose of this study was to analysis the content, the evaluation and the strengths and weaknesses of the Islamic religious education curriculum in the moral aspects of students. The type of research is a qualitative type and content analysis technic. The results of the research are students' morality material is found in Islamic religious education books starting from grade VII-IX. These materials begin human relations with God, human relationships, and human relationships with the environment. The evaluation used is of course a variety of evaluations ranging from assignments, multiple choice, descriptions, portfolios, and semester exams. The three advantages of each material are equipped with a concept map, integrated with tajwid science lessons, technology-based learning, assessments are carried out in various aspects, and parents have a role towards their children. While the weaknesses in the Asmaul Husna material are only 4 names out of 99 Asmaul Husna, the material related to other materials is not sequential, the implementation of the assessment only focuses on the aspect of knowledge, and many materials are the same.